From Taking Ownership to Decolonization: Looking Back Over Five Decades of Indigenous Post-secondary Education in Quebec - Ratel, Jean-Luc; Bacon, Marco; Pilote, Annie (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
In the early days soon after the release of the landmark policy paper Indian Control of Indian Education (1972), postsecondary studies among Indigenous people in Quebec were still new and relatively unknown. Against a backdrop of Indigenous communities starting to take ownership of their own services, the demand for postsecondary Indigenous graduates began to increase significantly, resulting in the development of tailored programs and services: the Amerindianization program led by UQAC in 1971 and the founding of Manitou College in 1973, for example, stand out as two major milestones. The distinctive linguistic reality of Quebec moreover soon became apparent, adding to the initial bilingual dimension (moving from an Indigenous language to an non-Indigenous one) the duality of a francophone and anglophone education system rooted in colonial history. Drawing on a review of literature on postsecondary Indigenous education in Quebec from 1972 to 2021, our analysis in the present article is framed around the changes that took place over these past five decades in programs and services provided by postsecondary institutions. Also discussed are issues involving Indigenous student paths marked by identity, systemic racism and discrimination. We note that in spite of sustained efforts by an increasing number of institutions, Indigenouspeople still face enduring barriers. We conclude with some thoughts on the university and the CEGEP as postsecondary institutions, their development model and their role in decolonizing and democratizing education.